2021
DOI: 10.3390/s21041225
|View full text |Cite
|
Sign up to set email alerts
|

Deskilled and Rapid Drug-Resistant Gene Detection by Centrifugal Force-Assisted Thermal Convection PCR Device

Abstract: Here we report the improved Cyclo olefin polymer (COP) microfluidic chip and polymerase chain reaction (PCR) amplification system for point-of-care testing (POCT) in rapid detection of Carbapenem-resistant Enterobacteriaceae (CRE). The PCR solution and thermal cycling is controlled by the relative gravitational acceleration (7G) only and is expected to pose minimal problem in operation by non-expert users. Detection is based on identifying the presence of carbapenemase encoding gene through the corresponding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, the right meniscus was not moving in parallel with the other meniscus due to fabrication problems. Aside from the fabrication issue, the microchannel behaved as was expected according to previous work (13,20).…”
Section: Thermal Convection Flow On CDsupporting
confidence: 67%
“…However, the right meniscus was not moving in parallel with the other meniscus due to fabrication problems. Aside from the fabrication issue, the microchannel behaved as was expected according to previous work (13,20).…”
Section: Thermal Convection Flow On CDsupporting
confidence: 67%
“… Lok et al (2012a) reported on the design of a magnetically actuated circular closed-loop PCR chip, in which a ferrofluid plug is driven by an external magnet that moves along the microchannel and four loops can carry out PCRs simultaneously. Espulgar et al (2021) fabricated an identical closed-loop channel on a centrifugal disk-like chip; this design can apply 106 thermal cycles in 15 min. The drawbacks of closed-loop PCR chips are the inconvenience of retrieving the solution and an asymmetrical reaction procedure in concentric channels when high-throughput testing is attempted.…”
Section: Rapid Dna Amplification Methodsmentioning
confidence: 99%
“…In many studies, fluorescent dye (such as calcein or SYBR Green) has been added to create a more conspicuous light green color for easy detection. Zhang M. et al (2021) embedded calcein-soaked paper in the reaction chamber for direct detection of LAMP products.…”
Section: Fluorescent and Colorimetric Detectionmentioning
confidence: 99%
“…For a microfluidic PCR, the thermal cycling time is calculated in minutes, and the size of the reactor is required in μL, whereas a microfluidic PCR is defined as γ [ 21 ]. The first type of reactor is termed as a stationary reactor, forced continuous flow PCR is the second type of reactor and the third type of reactor is composed of a free heat deportation system [ 21 , 22 , 23 , 24 ].…”
Section: Microfluidic Technology and Poctsmentioning
confidence: 99%